UPAYA PERLINDUNGAN HUKUM PENGELOLAAN WILAYAH DI KALIMANTAN TIMUR ( TINJAUAN HUKUM PERATURAN DAERAH PROVINSI KALIMANTAN TIMUR NOMOR 1 TAHUN 2016 TENTANG RENCANA TATA RUANG WILAYAH KALIMANTAN TIMUR 2016-2036 ) - Rustati Rustati (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT East Kalimantan was the region with the potential of natural resources are abundant. The wealth of natural resources be authorized to manage and develop their regions. Although it is undeniable that manage these natural resources are issues that become dynamics in governance. The issue of natural resorces becomes very important when associated with implementation between different level of goverment into the empirical facts for the goverment in achieving environmenrally sustainable development. The role of the provincial government that had been expected to be cen realized in line with expectations. Cooperation   beetween the governmentand stakeholders in the area have not materialized as it should be. Effort to involve stakeholders as stated in the act autonomy. Imagine, 1945 that the ability of local goverment to manage and utilize these resources will give effect to the areaof financial management. The potential of natural resources owned by the East Kalimantan Province becomes strategic when it can be managed and developed  optimally in supporting the wheels of government and developed of the region. Efforts legal protection zone management in Eas Kalimantan (Law review East Kalimantan Provincial Regulation No. 1 Year 2016 on Spatial Kaltim 2016-20136): (1) development is inseparable from the develoment regions of the world, investors wiil invest in areas the have the political conditions stable and supported by adequate resources (2) empowering comunities (3) approach to comunity emprowerment is a demand that must be met Good Govermance (4) Climate and good performance in the contruction needs to be run. Its characteristis is community participation, transparency, responsiveness and accountability.Keyword : Spatial Area, Protection Zone Management